The State of the World's Children 1993 - Grant, James P. (United Nations Children's Fund (UNICEF), 1993)
This item contains two parts: Part I – The State of the World’s Children 1993, which looks at 1. The age of neglect and the age of concern, 2. A common cause, 3. A movement for basic needs, and 4. The wider context. Part II – Statistics, which looks at economic and social statistics on the nations of the world, with particular reference to children’s well-being.
Keywords: Children